Evaluation of shea butter, olive oil and avocado oil enriched baby cleansing bar: real-world evidence from clinical practice across India - Shenoy, Manjunath; Gupta, Naveen P.; Sen, Dyotona; Choudhary, Sanjay (International Journal of Contemporary Pediatrics, 2025)
Background: Clinicians widely prescribe mild cleansers in India for baby skincare. Shea butter, olive and avocado oil-enriched baby cleansing bar is a gentle cleansing syndet bar with pH 5.5 formulated especially for infants’ delicate skin. Although efficacy and safety of this cleansing bar have been well studied, its real-world experience data are limited in India. Methods: This observational cross-sectional PAN India survey study included pediatricians and dermatologists who prescribed this cleansing bar (Cetaphil® Baby Mild Bar®) to their patients. Clinicians were given a nine-point questionnaire specific to their experience with this bar in routine practice. Results: Over 128 clinicians provided data on their experience with product for 572 children. Most children (45.3%) were between 1–4 years, followed by <12 months (36.3%). Cleansing bar was prescribed in children with both normal skin (61.2%) and those with pre-existing conditions such as atopic dermatitis, dry, and sensitive skin (38.8%). 84.1% of clinicians recommended its use for as long as required. Most clinicians (90%) indicated that cleansing bar did not cause skin dryness. Cleansing properties were rated as “excellent” by 66.8% of clinicians and “good” by 32.9%. 95.3% of physicians recommended use of this bar from day one of life. Clinicians and parental feedback reported benefits including improved moisturization, enhanced skin tone, reduced itchiness, and softer, smoother skin. Conclusions: Shea butter, olive and avocado oil-enriched baby cleansing bar (Cetaphil® Baby Mild Bar®) with pH 5.5 is safe, well-tolerated, and effective in infants and young children, including those with atopic dermatitis, dry and sensitive skin.